Evaluation on interleukin-6 and tumor necrosis factors-α level in saliva among age related macular degeneration patients - Krishnan, Sarojini (2020)
Introduction: Age related macular degeneration (AMD) is known as a leading cause of blindness in developed countries and the third leading cause of blindness worldwide, in elderly population more than 50 years of age. Multifactorial etiology involves in AMD pathogenesis includes both genetic backgrounds and environmental risk factors. Recent evidence has been showing that inflammation has a crucial role in AMD development and progression. Increased in Interleukin 6 (IL-6) and Tumor necrosis factor alpha (TNF-α) were associated with AMD. Saliva protein biomarkers are fast development novel technique for clinical diagnosis. Thus, identification of IL-6 and TNF-α in saliva perhaps provide insight the role of saliva sample as a diagnostic alternative in future. Objective: Our objective was to evaluate IL-6 and TNF-α level in saliva between AMD patients and Control group, and also in between Early and Late AMD. Besides that, to determine the relationship between IL-6 and TNF-α level in saliva with duration of AMD. Methods: A comparative cross-sectional study was conducted exclusively at a tertiary hospital in Malaysia, Hospital Universiti Sains Malaysia (USM) between January 2018 and May 2020. This study involved patients with Early AMD, Late AMD and Control group. Unstimulated saliva samples were collected. Laboratory analysis using commercial Human IL-6 and TNF-α ELISA kit (LEGEND MAXTM, Biolegend, Inc.) was performed to measure IL-6 and TNF-α levels in saliva. Statistical analysis was done using SPSS Inc Version 24. Results: A total of 92 patients were included into the study and 88 were analysed after data cleaning (Early AMD: 29 patients, Late AMD: 30 patients, Control: 29 patients). There was no significant difference of mean IL-6 and TNF-α level in saliva between AMD and Control group after adjusted with covariates. Mean IL-6 in saliva was significantly higher in Late AMD (8.64 SD 6.58 pg/ml) compared to Early AMD (5.07 SD 4.29 pg/ml) (p=0.017), however, it was not significant after adjusted with the covariates (p=0.173). There was no significant difference of mean TNF-α in saliva between Early and Late AMD ( -26.60 SD 1.29 pg/ml vs -26.13 SD 1.67 pg/ml, p=0.234). There was no significant association was found between duration of AMD with IL-6 and TNF-α level in saliva. Although few factors were significantly associated with IL-6 and TNF-α level in saliva on simple linear regression, however, none of the factors had significant association on multiple linear regression. Conclusion: This study showed that there was no significant associations between IL-6 and TNF-α level in saliva among AMD patients. AMD pathogenesis more confined to a local inflammatory process and ocular concentrations of inflammatory biomarkers in the pathological eye are not necessarily associated with systemic concentration. Furthermore, a large cohort study is needed for further evaluation to show the significant correlation between saliva inflammatory biomarkers level with ocular pathology.